2015
DOI: 10.1038/ncomms8601
|View full text |Cite
|
Sign up to set email alerts
|

Prediction model for aneuploidy in early human embryo development revealed by single-cell analysis

Abstract: Aneuploidies are prevalent in the human embryo and impair proper development, leading to cell cycle arrest. Recent advances in imaging and molecular and genetic analyses are postulated as promising strategies to unveil the mechanisms involved in aneuploidy generation. Here we combine time-lapse, complete chromosomal assessment and single-cell RT–qPCR to simultaneously obtain information from all cells that compose a human embryo until the approximately eight-cell stage (n=85). Our data indicate that the chromo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
94
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(105 citation statements)
references
References 70 publications
11
94
0
Order By: Relevance
“…Our proposed models are consistent with the live-imaging studies, which have uncovered atypical pronuclear evolution and aberrant natures of zygotic cytokinesis (Van Blerkom 1990;Hardy et al 1993;Athayde Wirka et al 2014;Vera-Rodriguez et al 2015). Zygotes derived from intra-cytoplasmic sperm injection (ICSI) of a single sperm cell can transit from a normal two pronuclei (2PN) to a tri-pronucleated phase (3PN) (Lammers et al 2014), indicating that endomitosis may cause multinucleation of zygotes.…”
Section: Wwwgenomeorgsupporting
confidence: 69%
See 1 more Smart Citation
“…Our proposed models are consistent with the live-imaging studies, which have uncovered atypical pronuclear evolution and aberrant natures of zygotic cytokinesis (Van Blerkom 1990;Hardy et al 1993;Athayde Wirka et al 2014;Vera-Rodriguez et al 2015). Zygotes derived from intra-cytoplasmic sperm injection (ICSI) of a single sperm cell can transit from a normal two pronuclei (2PN) to a tri-pronucleated phase (3PN) (Lammers et al 2014), indicating that endomitosis may cause multinucleation of zygotes.…”
Section: Wwwgenomeorgsupporting
confidence: 69%
“…Interestingly, 2PN ICSI zygotes can divide directly into three or four blastomeres even in the absence of dispermy, suggesting the formation of a tripolar spindle through the introduction of a supernumerary centriole. The cellular and molecular components of these noncanonical zygotic divisions are not yet known; however, the combination of live-cell imaging techniques that detect aberrant cleavages with state-of-the-art single-cell RNA assays are starting to yield deeper insight into the molecular mechanisms (Vera-Rodriguez et al 2015).…”
Section: Wwwgenomeorgmentioning
confidence: 99%
“…There is some evidence in the literature that structurally abnormal chromosomes can be one of the causes for disruption of the mitotic process [34]. But there are conflicting results of different studies about whether kinetic markers of embryo development can predict aneuploidy [35, 36]. The complexity of the matter of how aneuploidy and aberrant division patterns are intertwined is also investigated in the study of Chavez et al [37], which stresses that embryo fragmentation might be a response to aneuploidy.…”
Section: Discussionmentioning
confidence: 99%
“…However, in human somatic cells, the SAC delays mitosis in the presence of multipolar spindles (Kwon et al 2008), and aneuploid human embryos show delayed first mitotic divisions, together alluding that super-numerary centrioles may exist (Vera-Rodriguez et al 2015).…”
Section: Proof Onlymentioning
confidence: 99%
“…However, little is known about how these function during the remainder of early human preimplantation development, and some intriguing observations allude that centriole dysregulation may occur in embryos. Firstly, studies of fresh and vitrified human embryos have reported multipolar spindles and tri-directional anaphases (Chatzimeletiou et al 2012, Vera-Rodriguez et al 2015, which in somatic cells is symptomatic of too many centrosomes (Ganem et al 2009). Secondly, a recent genome-wide association study identified singlenucleotide polymorphisms in the sequence of PLK4, a key regulator of centriole duplication, to be associated with embryonic mitotic errors (McCoy et al 2015).…”
Section: Unusual Centriole Behaviour In Early Developmentmentioning
confidence: 99%